PENGEMBANGAN PRODUK OLAHAN JAGUNG MELALUI UJI KESUKAAN KONSUMEN - Rika Diananing Putri; R. Amilia Destryana (Journal of Food Technology and Agroindustry, 2019)
This study aims to develop corn processed into a product that is beneficial to the health of the body and to determine consumer preferences for functional drinks, namely corn yogurt. Functional food needs to get attention so that its use has the correct scientific evidence basis, claims are not misleading and do not encourage wrong consumption patterns. One of the development of processed corn is functional food products such as yogurt. In order to be accepted by consumers, a test of preference for color, texture, aroma and taste was carried out by adding 10%, 12% and 14% fullcream milk. Conclusions produced by the community / consumers prefer yogurt with the addition of 12% fullcream to color, texture and aroma, while for consumers' taste like the addition of fullcream at 14%. This is due to the addition of 14% sour and sweet taste fullcream is felt.